Relationship between work fatigue and manual dexterity in dental professionals: observational study: . - Sartorio, Francesco; Ferriero, Giorgio; Corna, Stefano; Dal Negro, Francesca; DeAngeli, Mario; Cudazzo, Andrea; Vercelli, Stefano (La Medicina del Lavoro, 2020)
Background: Neuro-muscular fatigue (ANM) in the upper limbs can cause impaired coordination and dexterity. The main purpose of the study was to investigate whether ANM induced by a working day produced a reduction in digital dexterity in a population of dental health workers (OSD). Secondary objective was to investigate whether there were relationships between any reductions in dexterity and independent socio-demographic variables (gender, age and profession). Methods: A cohort of OSD was assessed before and at the end of a working day of at least 7 hours using the Functional Dexterity Test (FDT). The effects of ANM (time), of the tested limb (dominance), and of their interaction on dexterity were investigated using two-way ANOVA. A multiple linear regression model was applied to explore the relationship between dexterity performance and independent variables. Results: A total of 50 OSDs were included. The net time of the FDT at the end of the day was always higher than in the morning. The ANOVA showed a significant difference for time (p <0.001) and side (p <0.001), but an effect from the interaction between the two factors was not identified (p = 0.428). The worsening of manual dexterity appears to be weakly correlated with age on both sides, and with the profession in the dominant limb. Conclusion: The ANM appears to have negatively affected the dexterity of both hands in the sample examined. The results of this study may be useful for planning the OSD’s work agenda more carefully.